2019
DOI: 10.1017/s0022149x19000853
|View full text |Cite
|
Sign up to set email alerts
|

Five new morphological types of virgulate and microcotylous xiphidiocercariae based on morphological and molecular phylogenetic analyses

Abstract: The phylogenetic position of most xiphidiocercariae from subgroups Cercariae virgulae and Cercariae microcotylae remains unknown or unclear, even at the family level. In this paper, we studied the morphology and molecular phylogeny of 15 microcotylous and virgulate cercariae (11 new and four previously described ones). Based on morphological and molecular data, we suggested five distinct morphological types of xiphidiocercariae, which are a practical alternative to Cercariae virgulae and Cercariae microcotylae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
3
10
0
1
Order By: Relevance
“…The phylogram indicated that four xiphidiocercariae samples may be classified into three families, namely, Lecithodendriidae, Pleurogenidae and Telorchiidae. Shared by these families, this cercarial morphotype can yield a high diversity of trematode fauna, congruent with the previous study (Shchenkov et al, 2019) mentioned above. Of these three families, the family Lecithodendriidae is noteworthy as a group of intestinal flukes in humans (Chai et al, 2009;Chai, 2019) and is generally found to infect amphibians, mammals (especially bats) and occasionally birds (Schell, 1970;Frandsen and Christensen, 1984;Chai, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The phylogram indicated that four xiphidiocercariae samples may be classified into three families, namely, Lecithodendriidae, Pleurogenidae and Telorchiidae. Shared by these families, this cercarial morphotype can yield a high diversity of trematode fauna, congruent with the previous study (Shchenkov et al, 2019) mentioned above. Of these three families, the family Lecithodendriidae is noteworthy as a group of intestinal flukes in humans (Chai et al, 2009;Chai, 2019) and is generally found to infect amphibians, mammals (especially bats) and occasionally birds (Schell, 1970;Frandsen and Christensen, 1984;Chai, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Xiphidiocercariae commonly infected a variety of snail species, 8 of the 11 infected snail species identified. Xiphidiocercariae can be subdivided into several subgroups based on their morphological and molecular characters (Hall and Groves, 1963;Schell, 1970;Frandsen and Christensen, 1984;Shchenkov et al, 2019). Shchenkov et al (2019) recently identified five xiphidiocercariae; four of these corresponded to actual digenean taxa (Lecithodendriidae, Microphallidae, Pleurogenidae and Prosthogonimidae), and the remaining subtype was classified as undescribed taxa, for the first time, based on molecular evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The cercaria of S. vicarium from P. americanista showed three penetration glands, a morphological feature that appears to be a synapomorphy in Stomylotrematidae (Pinto et al, 2015, this paper). The number of pairs of penetration glands would be (Heneberg et al, 2015;Kudlai et al, 2015;Dellagnola et al, 2019a;Shchenkov et al, 2020). The virgula organ does not follow a consistent pattern into Microphalloidea.…”
Section: Morphological Traitsmentioning
confidence: 94%
“…It has been hypothesized that the virgula is a synapomorphy from 'lecithodendriid-like' flukes, formally Lecithodendriidae, Gyrabascidae, Phaneropsolidae and Leyogonimidae (Lotz and Font, 2008). However, some cercariae of these taxa have no virgula (Kudlai et al, 2015;Dellagnola et al, 2019a;Shchenkov et al, 2020). Furthermore, the shape and size of this organ are highly variable (Shchenkov et al, 2020) indicating that this organ would have evolved independently several times.…”
Section: Morphological Traitsmentioning
confidence: 99%
See 1 more Smart Citation